On the zooplankton community of a mexican eutrophic reservoir, a seasonal survey - Suárez-Morales, Eduardo; Vázquez-Mazy, Amparo; Solís M., Eduardo (HIDROBIOLÓGICA, 2016)
The seasonal fluctuation in the zooplankton community of the J. A. Alzate Dam (México), an eutrophic reservoir, was studied during a year cycle (1986-1987). A total of wenty one species, belonging to Rotifera, Copepoda and Cladocera, were observed. These three groups showed sesonl density and distribution fluctutions. Zooplankton community was widely dominated by cladocerans, constituting more than 90% of the toal annual catch. The dominant species throughout the year was the cladoceran Moina macrocopa, with densities between 15,000 and 800,000 ind m-3, and peaks in summer an autumn. The highest densities of cladocerans and rotifers ocurred in autumn, when maximum temperatures took place. Some rotifers also show predation-related seasonal changes. The horinzontal distribution of zooplankton in the surveyed area seemed to be related with known distributional patterns. It is suggested that the structure of the local zooplankton community is strongly influenced by the dam depletion and filling seasonal rythms.